Qualidade fisiológica de sementes de soja resfriadas com diferentes tamanhos durante o armazenamento - Schauren, Dionéia (2011)
The artificial cooling has emerged as an alternative to maintaining the quality of seeds, whereas not always the storage environment, due to the conditions of temperature and relative humidity, this allows maintenance. Thus, the aim of this experiment was to evaluate the quality of soybean seeds subjected to cooling prior to storage. Seeds of soybean cultivar CD225RR from 5 to 6 mm sieves were subjected to cooling in cooler Coolseed brand, model PCS 12. A batch of seeds from the same source was not submitted prior to cooling. The seeds were stored in conventional storage Cooperative Agricultural Research Center - COODETEC of Rattlesnake for a period of 184 days between February August 2010. Every thirty days were sampled these stored seeds in order to evaluate the physiological quality (moisture content, weight of thousand seeds, infestation, germination, the first count germination, accelerated aging, electrical conductivity, tetrazolium test and volumetric weight). Analyses were performed in the laboratories of Food Technology and Seed State University of Western Paraná. In the warehouse, the air temperature ranged from 10 to 30 ° C. The cooling prior to storage and seed size resulted in significant differences in moisture content and in the first count germination of soybean cultivar CD 225RR. For mass of thousand seeds, germination, volumetric weight, electrical conductivity and accelerated aging effect was observed only in seed size. The use of cooling prior to storage did not improve the physiological quality of soybean cultivar CD225RR to the conditions under which the experiment was conducted